Applying Different Magnetic Water Densities as Irrigation for Aeroponically and Hydroponically Grown Strawberries - Tarek Mahrous Korany Mohamed; Jianmin Gao; Mohamed E. Abuarab; Mohamed Kassem; Essam Wasef; Wessam El-Ssawy (Agriculture, 2022)
Due to the scarcity of water, it is necessary to develop an environmentally friendly method for increasing water productivity and crop production. An experiment was conducted to assess the effects of different magnetic levels (magnetic water level 1 (MWL 1) = 3800 Gauss, magnetic water level 2 (MWL 2) = 5250 Gauss, and magnetic water level 3 (MWL 3) = 6300 Gauss, as well as normal water (NW) as a control) in combination with three soilless culture systems (a nutrient film technique (NFT) hydroponics system, a tower aeroponics system, and a pyramidal aeroponics system. The results showed that the utilization of magnetic water had significant effects on the yield and growth of strawberry plants The tower aeroponic system under MWL 3 produced the highest yield and water productivity, with increases of 80.9% and 89%, respectively, over the control. The tower aeroponic system under MWL 3 produced the highest yield and water productivity, with increases of 80.9% and 89%, respectively, over the control. In addition, as compared to the NW, the NFT system increased yield and water productivity by 71.1% and 79.3%, respectively, whilst the pyramidal system increased yield and water productivity by 66.87% and 82%, respectively. Furthermore, when compared to the control, the combination of the NFT system and magnetic water level 3 (MWL 3) resulted in the most leaves, largest stem diameter, and largest leaf area of the strawberry plants resulted in the most leaves, stem diameter, and leaf area of strawberry plants. In comparison to all other treatments, this combination produced the best fruit quality and yield, as well as its constituents, such as titratable acidity, total soluble solids, and fruit hardness. This study found that combining magnetic therapy with soilless culture techniques resulted in increased yield and water productivity. In addition, water and fertigation solution usage in the NFT, tower, and pyramidal systems dropped by 4.8%, 6%, and 4.8%, respectively. Furthermore, it enhanced plant morphology and plant quality.